'I started this, and I will end this': a phenomenological investigation of blue collar men undertaking engineering education as mature students. (4th March 2021) - Servant-Miklos, Virginie F. C.; Dewar, Eleanor F. A.; Bøgelund, Pia
ABSTRACT: Many blue-collar jobs, most of which are performed by men, are likely to be displaced by automation. These workers will, therefore, need to be retrained and reskilled, many of them choosing for engineering education as mature students. This paper uses Interpretive Phenomenological Analysis to draw a complex portrait of the experience of blue-collar men studying engineering as mature students in Denmark. We found that the participants faced considerable challenges in their engineering studies: they brought baggage from a challenging youth, from family traumas and educational failures; they felt alienation and cynicism about the world and saw their own possibilities for progress thereby limited; and they experienced difficulties with the contents and the process of the engineering curriculum. However, they persisted with faith in engineering education as a gateway to a better life and a sense of social responsibility as future engineers. The study concludes that more pro-active university support systems would alleviate the difficulties faced by such students.